Changes in brain-derived neurotrophic factors in schizophrenic patients with spiritual psychoreligious therapy - Rosyanti, Lilin; Hadi, Indriono; Akhmad; Faturrahman, Teguh; Hidayat, Arip (Journal of the Pakistan Medical Association, 2024)
Objective: To examine the effect of Spiritual Quranic Emotional Freedom Technique therapy on the level of brain-derived neurotrophic factor in schizophrenic patients. Method: The quasi-experimental study was conducted from August to December 2021 at the Polytechnic of Health, Kendari, Indonesia, and comprised patients of either gender aged >20 years who had been diagnosed with schizophrenia by psychiatrists using the text-revised version of the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders, had Brief Psychiatric Rating Scale score 50-60, and were part of the treatment programme at the polyclinic. They were divided into experimental group A and control group B. Patients in group A were given 30 days of Spiritual Quranic Emotional Freedom Technique therapy, while those in group B received only education about the spiritual therapy with the recommendation to listen to the Quran verses. A set of healthy controls memorizing the Quran was enrolled from the Islamic Boarding School, Kendari, and placed in group C. They were given education about the need to keep reading and learning the Quran. The intervention was done 2 times per week for 4 weeks. Serum brain-derived neurotrophic factor level for all groups and the Brief Psychiatric Rating Scale score for groups A and B were assessed at baseline and post-intervention. Data was analysed using SPSS 22. Results: Of the 30 subjects, 16(53.3%) were females and 14(46.7%) were males. There were 11(36.7%) subjects aged 31-40 years. Each of the 3 groups had 10(33.3%) subjects. There was a significant decrease in Brief Psychiatric Rating Scale scores in groups A and B post-intervention (p<0.000). There was a significant increase in serum brain-derived neurotrophic factor levels post-therapy in groups A and C (p<0.001), while in group B it was not significant (p=0.500). Conclusion: Spiritual Quranic Emotional Freedom Technique therapy could enhance clinical improvement and brain function in schizophrenic patients. Key Words: Spiritual, The Quran, Psychoreligious, Schizophrenic.